Conhecimento de enfermeiras sobre plano de parto: detectando fragilidades e capacitando para a prática profissional - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Aim: to identify the knowledge of nurses on Delivery Plan. Method: qualitative, descriptive and exploratory research, developed with 15 nurses who perform prenatal care in a municipality of western Rio Grande do Sul. Data collection took place in April and May, through semi-structured interviews and the analysis was of content in thematic modality. Results: three categories emerged: Birth Plan? Detecting weaknesses: it addresses the lack of knowledge by nurses on the subject; Enabling for professional practice: shows the interest of nurses in getting qualified; Possibilities and Weaknesses for implantint Childbirth Plan: highlights the pros and cons evidenciated. Final considerations: the study allowed deepening the theme, promoting the reflection with the professional who are included in health care, providing opportunities to review their practices.
Knowledge of nurses on delivery plan: detecting weaknesses andEmpowering for professional practice
Keywords: Enfermagem obstétrica; Parto humanizado; Educação pré-natal; Cuidado pré-natal; Obstetric nursing; Humanizing delivery; Prenatal education; Prenatal care; Enfermagem; Nursing; CNPQ::CIENCIAS DA SAUDE